Pretest probability for patients with suspected obstructive coronary artery disease: re-evaluating Diamond-Forrester for the contemporary era and clinical implications: insights from the PROMISE trial - Foldyna, Borek; Udelson, James E.; Karády, Júlia; Banerji, Dahlia; Lu, Michael T.; Mayrhofer, Thomas; Bittner, Daniel O.; Meyersohn, Nandini M.; Emami, Hamed; Genders, Tessa S.S.; Fordyce, Christopher B.; Ferencik, Maros; et al. (European Heart Journal - Cardiovascular Imaging, 2019)
AIMS: To update pretest probabilities (PTP) for obstructive coronary artery disease (CAD ≥ 50%) across age, sex, and clinical symptom strata, using coronary computed tomography angiography (CTA) in a large contemporary population of patients with stable chest pain referred to non-invasive testing. METHODS AND RESULTS: We included patients enrolled in the Prospective Multicenter Imaging Study for Evaluation of Chest Pain (PROMISE) trial and randomized to CTA. Exclusively level III-certified readers, blinded to demographic and clinical data, assessed the prevalence of CAD ≥ 50% in a central core lab. After comparing the recent European Society of Cardiology-Diamond and Forrester PTP (ESC-DF) with the actual observed prevalence of CAD ≥ 50%, we created a new PTP set by replacing the ESC-DF PTP with the observed prevalence of CAD ≥ 50% across strata of age, sex, and type of angina. In 4415 patients (48.3% men; 60.5 ± 8.2 years; 78% atypical angina; 11% typical angina; 11% non-anginal chest pain), the observed prevalence of CAD ≥ 50% was 13.9%, only one-third of the average ESC-DF PTP (40.6; P < 0.001 for difference). The PTP in the new set ranged 2-48% and were consistently lower than the ESC-DF PTP across all age, sex, and angina type categories. Initially, 4284/4415 (97%) patients were classified as intermediate-probability by the ESC-DF (PTP 15-85%); using the PROMISE-PTP, 50.2% of these patients were reclassified to the low PTP category (PTP < 15%). CONCLUSION: The ESC-DF PTP overestimate vastly the actual prevalence of CAD ≥ 50%. A new set of PTP, derived from results of non-invasive testing, may substantially reduce the need for non-invasive tests in stable chest pain.
CRIS-Team Scopus Importer:2019-07-16
Keywords: computed tomography angiography; coronary stenosis; Diamond and Forrester; obstructive coronary artery disease; stable chest pain